Synthése et caractérisation des nanoparticules d’oxyde de cobalt pour des applications catalytiques - ARID, KARIMA; TEDJINI, SAFA; DJOUADI, KALTOUM; DJEDIDI, BOUTHAINA; LAHLOUH, INASS (université d'eloued, 2023)
"Cobalt oxide nanoparticles (Co3O4) are semi-conductor materials, given their important structural, chemical, physical, optical and magnetic properties which differ from those of other homologous materials have aroused potential interest these last years. With its magnetic moment aligned in the antiferromagnetic order, its properties have a significant impact in device applications such as gas sensors, information storage components, decontamination catalysts environmental protection and solar panel absorbers. Keywords: " "الجسيمات النانوية لأكسيد الكوبالت (Co3O4) هي مواد شبه موصلة, نظرا لخصائصها الهيكلية والكيميائية والفيزيائية والبصرية والمغناطسية التي تختلف عن تلك الخاصة بالمواد المتماثلة الأخرى, فقد أثارت الاهتمام المحتمل في السنوات الأخيرة. من خلال محاذاة عزمها المغناطيسي بالترتيب المغنطيسي المضاد, فان خصائصها لها تأثير كبير في تطبيقات الأجهزة مثل مستشعرات الغاز, ومكونات تخزين المعلومات , ومحفزات إزالة التلوث البيئي , وامتصاص الألواح الشمسية. "
مذكرة ماستر هندسة كيميائيةDes thèses génie chimique
Keywords: "Cobalt oxide, Co3O4 , Decontamination, Catalysts, Sensors. "; الكلمات المفتاحية: أكسيد الكوبالت, Co3O4 , تطهير, محفزات, مجسات.